(untitled) (Sahel Journal of Life Sciences FUDMA, 2026)
Gastrointestinal parasitism remains an important constraint to small ruminant productivity; however, data on parasite occurrence in goats in the Maldives are lacking. This study investigated the prevalence of endoparasites in goats reared in Naifaru, Maldives, using standard parasitological techniques. A total of 32 faecal samples were collected from goats across six farms and examined for endoparasites employing direct faecal smear, simple faecal flotation, and sedimentation methods. The use of multiple diagnostic approaches improved detection sensitivity for both protozoan and helminth infections. Data obtained were analyzed descriptively to determine parasite occurrence and overall prevalence. The results indicated the presence of Eimeria spp. as the only detected endoparasite, while no helminth eggs or larvae were observed across all samples examined. The overall prevalence of gastrointestinal endoparasites was low, with infections limited to intracellular protozoan parasites. The absence of helminth infections suggests either minimal exposure to infective stages or effective natural or management-related control within the study area. In conclusion, this study provides baseline data on gastrointestinal parasites in goats in Naifaru, Maldives, revealing a low prevalence of endoparasitic infections and no detectable helminthiasis. These findings highlight the need for continued surveillance and the implementation of appropriate management strategies to prevent potential parasite outbreaks and sustain goat productivity in the region.